Pengaruh Environmental, Social, Governance (ESG), Struktur Modal, dan Profitabilitas terhadap Nilai Perusahaan pada Sektor Pertambangan - Annisa Rohimatu Zahra; Sri Hasnawati; Ahmad Faisol (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Multidimensional pressures faced by the mining sector, ranging from commodity price volatility, high capital intensity, sustainability demands, to regulatory uncertainty arising from geopolitical dynamics, which collectively contribute to fluctuations in firm value, constitute the background of this study. This research focuses on examinin how capital structure, profitability, and environmental, social, and governance (ESG) factors affect the firm value of mining businesses listed on the Indonesia Stock Exchange between 2019 and 2024. A quantitative technique using panel data regression analysis on secondary data from business sustainability reports and financial statements is employed. The study’s findings indicate that profitability, proxided by Return on Assets (ROA) and capital structure that proxied by Long-term Debt to Equity Ratio (LDER) has a positive and significant impact on firm value, and ESG has no significant impact on firm value. These results show that when assessing companies, investors continue to give more weight to financial considerations than non-financial ones. According to the research’s findings, in order for businesses to generate value over time, they must optimize capital structure management, increase profitability, and improve the caliber of ESG implementation.